Emulation of Synchronous Generator for Frequency Control of Smart Microgrids - Frack Auger, Pablo Federico (2013)
Microgrids (MGs) are emerging as a new paradigm for the integration of Distributed Generation (DG) assets. These novel grid structures present significant benefits to the Electric Power System. One of the most important benefits is the reliability improvement due to the capacity of islanded standalone operation. Nevertheless, this stand-alone operation can bring some problems related to frequency control, especially in MGs with many DG units connected through power electronics interfaces. In this case, the frequency control capacity and hence the stability margins are drastically reduced. This paper presents the design and implementation of a proton exchange membrane fuel cell integrated with supercapacitor energy storage and its control strategy for the frequency control of ac-MGs.